Hubungan Tinggi Alveolar Mandibula Terhadap Retensi Gigi Tiruan Penuh Pada Pasien Rumah Sakit Gigi dan Mulut Universitas Andalas - Salsabilla Septia; Eni Rahmi; Bambang Bambang (Faculty of Dentistry Universitas Andalas, 2019)
Complete denture wearers were mostly complained with the uncomfortable and less retention of their denture especially mandibular denture. Alveolar ridge resorption leads to decrease in the size of denture-bearing area, therefore reducing denture retention. There are many factors that cause loss retention, which are closely related to alveolar ridge height. The aim of the study is to determine the relationship between mandibular residual ridge height and complete denture retention in Andalas Dental Collage and Hospital. Methods: This study used a cross sectional design, with total sampel of 30 complete denture wearers. Samples was selected through Consecutive Sampling Method. Data was collected by using medical record, panoramic radiograph, and denture retention examination that were analyzed by Chi-Square test with p<0.05. Results: There was not a significant relationship between mandibular residual ridge height and denture retention (p>0.05). The conclusion of this study was the denture retention is not associated with mandibular residual ridge height in Andalas Dental Collage and Hospital.